A step towards achieving SDG 2030 agenda: Analyzing the predictive power of information globalization amidst technological innovation-environmental stewardship nexus in the greenest economies. (1st June 2023) - Ramzan, Muhammad; Ullah, Sami; Raza, Syed Ali; Nadeem, Muhammad
Abstract: Through the transition of novel ideas, products, technologies, and business models, info-globalization facilitates the flow and expansion of cross-border information and resources. In the meantime, this stimulates the potential of informational globalization and the internet for environmental and other technological advancements, and assists to the realization of cleaner and greener production and consumption. However, prior studies have completely disregarded this facet of globalization. Thus, this novel study evaluates the role of technological innovation (TIN) and information globalization (ING) in predicting ecological footprints (EFP) and carbon emissions (CO2) in the world's top ten greenest economies. Besides, this study also unveils the moderating role of TIN and ING for environmental sustainability. The novel research employs non-parametric causality-in-quantiles approaches on quarterly data from 1994Q1 to 2019Q4 in order to quantify for causality-in-mean and causality-in-variance, since there may be no causation at first moment, but higher-order interdependencies may exist. The findings revealed that TIN and ING possess significant predictive potential for both ecological footprint and carbon emissions, indicating asymmetric predictability over environmental sustainability. Moreover, TIN and ING asserted a significant interaction role when it comes to predicting pollution levels in chosen countries. Overall, it is essential to note that natural resource conservation and pollution mitigation via green and technical innovation become a dilemma since pollution has no boundaries and will always stoke fires beyond them. The provision of financial and R&D assistance, as well as the use of mass and social media to raise awareness not only in their own regions but also in neighboring countries, might contribute to the achievement of SDG 13 and Cope26's ambition of cutting pollution by 2030. Highlights: The predictability power of information globalization and technological innovation for environment stewardship is examined. The quarterly data of top 10 greenest economies are studied from 1994Q1 to 2019Q4. Technological innovation and information globalization have strong predictive power for environmental footprint. The information globalization and technological innovation interaction is significantly predicting environmental quality. Several policy pathways have been proposed to safeguard the environment by 2030.